Kamus praktis Inggris-Indonesia : disertai penggunaannya dalam kalimat / Vincent Sudarna, Dian Indarini ; editor Flora Maharani, Barli Bram. - VINCENT SUDARNA; Dian Indarini; Flora Maharani; Barli Bram (Kanisius, 2015)
199 hlm. ; 19 cm